The effect of nano-curcumin on HbA1c, fasting blood glucose, and lipid profile in diabetic subjects: a randomized clinical trial - Hamid Reza Rahimi; Amir Hooshang Mohammadpour; Mostafa Dastani; Mahmoud Reza Jaafari; Khali Abnous; Majid Ghayour Mobarhan; Reza Kazemi Oskuee (Mashhad University of Medical Sciences, 2016)
Objective: Diabetes mellitus is defined as a group of metabolic diseases characterized by hyperglycemia resulting from defects in insulin secretion, insulin action, or both or insulin resistance. Curcumin inhibits NF-κB signaling pathway. The aim of this study is evaluation of the effect of Nano-curcumin on HbA1C, fast blood glucose and lipid profile in diabetic patients. Materials and Methods: Seventy type-2 diabetic patients (fasting blood glucose (FBG) ≥ 126 mg/dL or 2-hr postprandial blood glucose ≥200 mg/dl) randomly receivedeither Curcumin (as nano-micelle 80 mg/day) or placebo for 3 months in a double blind randomized clinical trial. Fasting blood glucose, HbA1C, and lipids profile were checked before and after the intervention. Data analyses, including parametric and nonparametric tests were done using the SPSS 11.5 software. A p value < 0.05 was regarded as statistically significant. (RCT registration code: IRCT2013081114330N1) Results: Mean age, BMI, FBG, total cholesterol (TC), triglyceride (TG), LDL, HDL, HbA1c , and  sex and had no significant difference at the baseline between the groups. In Nano-curcumin group, a significant decrease was found in HbA1C, FBG, TG, and BMI comparing results of each subject before and after the treatment (p